Ecutaneous treatment of injuries no bile duct neoplasms - Tiscornia, Eduardo (Cirugía del Uruguay, 1990)
Non neoplasic biliay /esion are sometimes dificult to reat by surgey. Surgical repair of benign strictures is associated with a 25% morbiiy and a 13% of mortality. Seventeen patients were treatd wih percuaneous biliay catheters using the transhepatic rout or a T tube rack. Non neoplasic biliar obstrucions dificult to repair by sugey must be treated by interentional aiology alone or in combination with surgery